The role of dual-specificity phosphatase 6 (DUSP6) in metastasis and metabolism of pancreatic cancer cells - Ruckert, Mariana Tannús (2022)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive tumor and is majorly caused by the constitutive activation of mutant KRAS - found in more than 90% of PDAC cases. The undruggability of KRAS mutations has led to efforts of finding new therapeutic targets that focus on downstream molecules in the MAPK pathways. The regulation of these kinase activities is orchestrated by a negative feedback network played by a series of protein tyrosine kinases (PTKs) and protein tyrosine phosphatases (PTPs), which in turn activate and inhibit the phosphatase function. DUSP6 is a dual-specificity phosphatase that regulates ERK1/2 phosphorylation and, therefore, RAS pathway activation. Data from different PDAC datasets revealed that DUSP6 is overexpressed in metastatic tumor samples compared to primary tumor samples and to non-tumoral pancreatic tissue. Overall survival analysis indicated that patients with high DUSP6 expression have a worse prognosis than patients with low DUSP6 expression, reaffirming its clinical relevance. Moreover, we observed that DUSP6 is overexpressed in the quasimesenchymal/stromal subtype, which was previously described to be correlated with the glycolytic phenotype and the worst prognosis among all the other described PDAC subtypes. Considering the aforementioned, we hypothesized that DUSP6 could play a role in metabolism reprogramming in PDAC and, therefore, induce a more aggressive phenotype, leading to metastasis development. To investigate DUSP6 role in metastasis development and progression we developed DUSP6 stable knockdown in PDAC cells lines and performed genotypic and phenotypic analysis to evaluate metastatic and metabolic behaviors. Surprisingly, we observed different phenotypes among the cell lines used, which we believe is derived from the different genetic backgrounds and metabolic subtypes involved. Overall, results indicate that DUSP6 play a role in the metastatic process in PDAC, modifying phenotypes that are closely related to the cells capacity to survive and thrive in an unfamiliar environment. Also, DUSP6 plays a role in the metabolic reprogramming of these cells, as we observe that its knockdown induces glycolysis in these cells under blockage of the mitochondrial respiration. Nevertheless, the mechanism behind these changes remains to be further investigated.